Applications of low-temperature thermochemical energy storage systems for salt hydrates based on material classification: A review. (15th January 2021) - Lin, Jianquan; Zhao, Qian; Huang, Haotian; Mao, Hongzhi; Liu, Yexin; Xiao, Yimin
Abstract: Thermochemical energy storage (TCES) systems are an advanced energy storage technology that address the potential mismatch between the availability of solar energy and its consumption. As such, it serves as the optimal choice for space heating and domestic hot water generation using low-temperature solar energy technology. Among all TCES systems, the most widely used are solid/gas sorption systems utilizing salt hydrates. However, the different basic properties of each material, application site, applicable reactor form, and design and control strategy of system prototypes depend on material characteristics. This study established a reasonable classification of salt hydrates for TCES systems, summarizing the properties of materials, suitable types of reactors, applications, and optimization of system prototypes based on material characteristics. Herein, TCES applications based on salt hydrates are comprehensively reviewed, elucidating the current state of the development of TCES applications for each material. Directions for target-oriented design and optimization of TCES systems are also discussed.